2009
DOI: 10.1371/journal.pone.0005808
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hippocampal and Behavioral Excitability by Cyclin-Dependent Kinase 5

Abstract: Cyclin-dependent kinase 5 (Cdk5) is a proline-directed serine/threonine kinase that has been implicated in learning, synaptic plasticity, neurotransmission, and numerous neurological disorders. We previously showed that conditional loss of Cdk5 in adult mice enhanced hippocampal learning and plasticity via modulation of calpain-mediated N-methyl-D-aspartic acid receptor (NMDAR) degradation. In the present study, we characterize the enhanced synaptic plasticity and examine the effects of long-term Cdk5 loss on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…However, both Cdk5 mutant mouse models exhibit seizures. Hawasli et al proposed that an acute increase in p25 levels in their mouse model during seizure activity is a compensatory mechanism, and long-term loss of Cdk5 also results in a reduction in p25 (Hawasli et al, 2009). While we have not yet examined the relationship of p35 to p25 levels in our Cdk5f/f/CW2 animals, we cannot exclude the possibility that cleavage of p35 to p25 is altered under neurotoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, both Cdk5 mutant mouse models exhibit seizures. Hawasli et al proposed that an acute increase in p25 levels in their mouse model during seizure activity is a compensatory mechanism, and long-term loss of Cdk5 also results in a reduction in p25 (Hawasli et al, 2009). While we have not yet examined the relationship of p35 to p25 levels in our Cdk5f/f/CW2 animals, we cannot exclude the possibility that cleavage of p35 to p25 is altered under neurotoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As a noninvasive metabolic imaging technique with clinical acceptance, FDG-PET demonstrated clear perturbations in glucose metabolism, prompting our further study of the effects of p35 KO on mesocorticolimbic circuitry and function. The hypermetabolic brain activity of p35 −/− mice may result from reduced Cdk5/p35-dependent inhibition of neuronal excitability (62-63). We also revealed that p35 KO caused increased mesolimbic connectivity and PFC neurotransmitter content possibly necessitating an increase in supportive energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Acute coronal brain slices and DG GCL recordings were performed as described previously (40). Briefly, recordings were performed on 400‐μm brain slices kept at 32°C in artificial cerebrospinal fluid (ACSF) containing 124 mM NaCl, 2 mM KCl, 2 mM MgSO 4 , 1.25 mM NaH 2 PO 4 , 26 mM NaHCO 3 , 2 mM CaCl 2 , 10 mM glucose, and a gas mixture of 95% O 2 and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%